Innovation in Planning and Development of Religious Education Based on Local Wisdom: Mambangkik Batang Tarandam Efforts - Fikar, M.; Ritonga, Mahyudin (Al-Hijr: Journal of Adulearn World, 2024)
Since the founding of the Unitary State of the Republic of Indonesia, the Minang people have played a significant role and contributed to building and fulfilling the independence of the Unitary State. However, in the last few decades, the position of the Minang people has faded in the national arena, both in the fields of education, religion, politics, economics, and other fields. Therefore, these roles and contributions need to be realized again, but producing figures with strengths in specific fields is challenging. Based on several existing theories, education is a strategic step in building competent individuals. In line with that, this article will analyze how innovative planning and development of religious education is based on local wisdom as an effort to mambangkik Batang Tarandam. The research was carried out using library research. Namely, data was collected from various books and articles published by multiple publishers. The data was analyzed using comparative techniques. For example, the researcher conducted a study by comparing several opinions to find the researcher's statement. The results of the analysis conclude that religious education based on local wisdom can potentially help develop Batang Tarandam. This finding is based on the history of Minangkabau figures who have made history in developing the Unitary State of the Republic of Indonesia based on surau-based education.